PENGARUH PER, ROA, ROE, DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM PADA PERUSAHAAN SUBSEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BEI PERIODE 2021-2024 - Susan Susan; Dicky Arisudhana (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of Price to Earning Ratio (PER), Return on Assets (ROA), Return on Equity (ROE), and Firm Size on Stock Returns in Consumer Non-Cyclicals sector companies in the Food and Beverage subsector listed on the Indonesia Stock Exchange (IDX) for the period 2021-2024. The research method used is quantitative with associative approaches. The sampling technique was carried out by purposive sampling, resulting in 56 companies as samples. The data used is secondary data obtained from financial statements. The results showed that partially PER has a negative and significant effect on stock returns. ROA has a positive and significant effect on stock returns. ROE and firm size have no effect on stock returns.